(3f+2)(f-2)=0

Simple and best practice solution for (3f+2)(f-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3f+2)(f-2)=0 equation:


Simplifying
(3f + 2)(f + -2) = 0

Reorder the terms:
(2 + 3f)(f + -2) = 0

Reorder the terms:
(2 + 3f)(-2 + f) = 0

Multiply (2 + 3f) * (-2 + f)
(2(-2 + f) + 3f * (-2 + f)) = 0
((-2 * 2 + f * 2) + 3f * (-2 + f)) = 0
((-4 + 2f) + 3f * (-2 + f)) = 0
(-4 + 2f + (-2 * 3f + f * 3f)) = 0
(-4 + 2f + (-6f + 3f2)) = 0

Combine like terms: 2f + -6f = -4f
(-4 + -4f + 3f2) = 0

Solving
-4 + -4f + 3f2 = 0

Solving for variable 'f'.

Factor a trinomial.
(-2 + -3f)(2 + -1f) = 0

Subproblem 1

Set the factor '(-2 + -3f)' equal to zero and attempt to solve: Simplifying -2 + -3f = 0 Solving -2 + -3f = 0 Move all terms containing f to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3f = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3f = 0 + 2 -3f = 0 + 2 Combine like terms: 0 + 2 = 2 -3f = 2 Divide each side by '-3'. f = -0.6666666667 Simplifying f = -0.6666666667

Subproblem 2

Set the factor '(2 + -1f)' equal to zero and attempt to solve: Simplifying 2 + -1f = 0 Solving 2 + -1f = 0 Move all terms containing f to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1f = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1f = 0 + -2 -1f = 0 + -2 Combine like terms: 0 + -2 = -2 -1f = -2 Divide each side by '-1'. f = 2 Simplifying f = 2

Solution

f = {-0.6666666667, 2}

See similar equations:

| AX-D+BX=C | | g(x)=2ln(x)+3ln(x+4) | | -2x+10=-5x+1 | | 2(3-4x)+10=32-5x+7 | | (x-1)(x+3i)(x-3i)=equation | | 9=-4r-5r | | 12n=-288 | | 3x(5-3a)+5=2x-a | | M-42=14 | | -8k=48 | | 2300=P*.075*10 | | 4000=P*.03*4 | | (x+3)(x+2)(x-(1-i))=equation | | w(2w)=64 | | 5y+2x=84 | | I=3400*.04*3 | | -7(10+v)=-231 | | I=3400*.0 | | 210=P*.08*7 | | 39x+2+49x+2=180 | | 5(x-3)+10=2(3x-4) | | 6+2u=-4 | | x(x+5)=105 | | 5x+7-8(x+1)=6x+3 | | 11x+9+12x+3=180 | | X+(X+10)+96=180 | | (X+5)(2X+15)(2X+10)=180 | | 18=x^2+1 | | (7X+1)+38+109=180 | | 17=x^2 | | -8=v-7 | | -5(5+x)=-40 |

Equations solver categories